2019
DOI: 10.3390/jmse7090282
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Polycyclic Aromatic Hydrocarbons in Sunken Oils in the Presence of Chemical Dispersant and Sediment

Abstract: The formation of sunken oils is mainly dominated by the interaction between spilled oils and sediments. Due to their patchiness and invisibility, cleaning operations become difficult. As a result, sunken oils may cause long-term and significant damage to marine benthonic organisms. In the present study, a bench experiment was designed and conducted to investigate the quantitative distribution of polycyclic aromatic hydrocarbons (PAHs) in sunken oils in the presence of chemical dispersant and sediment. The oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The growing global production and consumption of crude oil and its refined products have generated public concern about the effects of potential oil spills on marine ecosystems. Oil slicks from an accidental oil spill can reach coastal habitats through the action of wind, waves, and currents [1][2][3], and subsequently cause disastrous impacts on coastal zone and human activities. For instance, the 2010 Xingang Port oil spill in Dalian (China) caused more than 1500 t crude oil spilled into the Yellow Sea, resulting in severe losses of marine aquaculture in Liaoning Province.…”
Section: Introductionmentioning
confidence: 99%
“…The growing global production and consumption of crude oil and its refined products have generated public concern about the effects of potential oil spills on marine ecosystems. Oil slicks from an accidental oil spill can reach coastal habitats through the action of wind, waves, and currents [1][2][3], and subsequently cause disastrous impacts on coastal zone and human activities. For instance, the 2010 Xingang Port oil spill in Dalian (China) caused more than 1500 t crude oil spilled into the Yellow Sea, resulting in severe losses of marine aquaculture in Liaoning Province.…”
Section: Introductionmentioning
confidence: 99%
“…PAH bioaccumulation potential is also understood to be higher in sedentary filter-feeding organisms (Honda and Suzuki 2020). Gao et al (2019) demonstrated that the interaction of suspended sediment with dispersant promotes the sinking of oil thereby facilitating entrainment in sediments, the content of PAHs increasing with increasing dispersants-to-oil ratio. Few studies available (e.g., Falk-Petersen et al 2007;Nørregaard et al 2015) indicate that PAH metabolism may be inhibited in organisms exposed to dispersant-oil mixtures to some degree, potentially facilitating trophic bioaccumulation.…”
Section: Bioaccumulation Of Contaminantsmentioning
confidence: 99%
“…3 Via whatever approach, the sunken oil is so difficult and expensive to nd and clean up that it further contaminates sediments and presents a toxic risk to benthic species. 4,5 OPAs can be generally classied as oil-mineral aggregates (OMAs) and marine oil snow (MOS). OMAs specically refer to micro-aggregates (typically <50 mm) that are formed by dispersed oil droplets and suspended mineral particles such as kaolinite, quartz and montmorillonite.…”
Section: Introductionmentioning
confidence: 99%
“…3 Via whatever approach, the sunken oil is so difficult and expensive to find and clean up that it further contaminates sediments and presents a toxic risk to benthic species. 4,5…”
Section: Introductionmentioning
confidence: 99%